2023
DOI: 10.1021/acs.jafc.3c02466
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Soybean Oil Evoked Hepatic Fatty Acid Metabolism Disturbance in Rats and their Offspring

Feng Gao,
Xin Guan,
Wentao Zhang
et al.

Abstract: The oxidation of fats and oils is an undisputed subject of science, given the effect of oxidized fats and oils on food quality and safety. This study aimed to determine whether maternal exposure to oxidized soybean oil (OSO) causes lipid metabolism disorders in the liver and whether this lipid metabolism disorder can be transmitted to offspring or even worsened. A total of 60 female Sprague–Dawley (SD) rats were divided randomly into four groups in this study. Treatment groups received a pure diet of OSO with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…52 53,54 In this study, we found that the OSO challenge significantly increased the piglet liver H 2 O 2 content and markedly decreased SOD and CAT activities. This is similar to the findings in our prior research that maternal exposure to OSO resulted in higher H 2 O 2 levels and lower activity of CAT and SOD in the liver of offspring, 30 whereas Res supplementa- tion in the OSO group improved the content of H 2 O 2 and restored the CAT and SOD activities. The finding was also supported by Fu et al, who found that Res enhanced the levels of antioxidants SOD and CAT and protected rats from ROS.…”
Section: ■ Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…52 53,54 In this study, we found that the OSO challenge significantly increased the piglet liver H 2 O 2 content and markedly decreased SOD and CAT activities. This is similar to the findings in our prior research that maternal exposure to OSO resulted in higher H 2 O 2 levels and lower activity of CAT and SOD in the liver of offspring, 30 whereas Res supplementa- tion in the OSO group improved the content of H 2 O 2 and restored the CAT and SOD activities. The finding was also supported by Fu et al, who found that Res enhanced the levels of antioxidants SOD and CAT and protected rats from ROS.…”
Section: ■ Discussionsupporting
confidence: 91%
“…This is similar to our previous findings that lipid vacuoles were in the cytoplasm of offspring liver cells after the maternal challenge with OSO. 30 In the OSO + Res group, membrane integrity improved and cytoplasmic vacuolization was reduced after Res supplementation.…”
Section: ■ Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, the pathogenicity of the strains should be tested. According to previous reports [ 44 ], a strain was considered pathogenic if the animals in the test group exhibited signs of toxicity or died during the experiment or if there were significant differences in physiological indicators such as body weight between the test group and control group. Our in vivo trial revealed that oral administration of B. siamensis MZ16 to mice did not result in adverse effects.…”
Section: Discussionmentioning
confidence: 99%